1977
DOI: 10.1002/app.1977.070210120
|View full text |Cite
|
Sign up to set email alerts
|

Bimodal character of polyester–solvent interactions. I. Evaluation of the solubility parameters of the aromatic and the aliphatic ester residues of poly(ethylene terephthalate)

Abstract: SynopsisThe Hildebrand and the Hansen solubility parameters of the aromatic and the aliphatic ester residues of poly(ethy1ene terephthalate), PET, are evaluated and compared to those determined experimentally. The interactions of nonaqueous solvents with the aromatic and aliphatic ester residues of PET are also described in terms of their relative basicity and acidity in the Lewis sense, where the aromatic residue may be taken as a Lewis acid and the aliphatic ester residue may be taken as a Lewis base.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1977
1977
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The solubility parameters of random copolymer could be calculated as the intermediate between that of the homopolymer constituents (Knox, 1977; Barton, 1985), and Ho et al (1991) confirmed this assumption through experiments on the methacrylonitrile/methacrylic acid copolymer system. We also predict the grafted copolymer solubility change by the parameters, and give a suitable solubility for a separating system to the membrane.…”
Section: Introductionmentioning
confidence: 77%
“…The solubility parameters of random copolymer could be calculated as the intermediate between that of the homopolymer constituents (Knox, 1977; Barton, 1985), and Ho et al (1991) confirmed this assumption through experiments on the methacrylonitrile/methacrylic acid copolymer system. We also predict the grafted copolymer solubility change by the parameters, and give a suitable solubility for a separating system to the membrane.…”
Section: Introductionmentioning
confidence: 77%
“…These results show high crystallization inducement of PEG400. Downloaded by [Chulalongkorn University] at 05:44 03 January 2015 It was reported that the chain of PET can be considered to consist of two segments with different solubility parameters: 20.2 (J/cm 3 ) 1/2 for aromatic segment, and 24.8 (J/cm 3 ) 1/2 for aliphatic segment [27,28] . As Table 2 shows, among the third components that we added, benzyl alcohol has a similar solubility parameter as the aromatic segment of PET, naphthalene and PEG have similar solubility parameters as the aliphatic segment, and dimethyl phthalate has the same solubility parameter as the whole PET chain.…”
Section: Effect Of Different Third Components In Tfa Solutionmentioning
confidence: 99%
“…As shown in Table 1 , on fast quenching in a test tube, the gelation of 2.1 N PET solutions of 5 to 10 wt% concentration in various solvents can be classifled into two types: 1) solutions that form translucent gels at temperatures above the melting point of solvent, and 2) solutions that turn turbid, followed by particle precipitation. It has been reported that PET has bimodal solubility parameter distribution with interaction maxima at 6 values of 20.2 and 24.8 (J/cm3)'/', which are assigned to the aromatic and the aliphatic residues of PET, respectively (12,13). It is interesting to find that the solvents of type 1 behavior in Table 1 have solubility parameter Values of about 20 ( J / c~~) ' /~, which is close to the value of the aromatic residue in PET.…”
Section: General Obsenmtion Of Gelation Phenomenamentioning
confidence: 99%